EFEKTIVITAS DINAS KOMUNIKASI DAN INFORMATIKA DALAM MENERAPKAN LAYANAN ASPIRASI DAN PENGADUAN ONLINE RAKYAT (LAPOR) DI KABUPATEN INDRAGIRI HULU - Alhafiz Agung Zeniar; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The Indragiri Hulu district government is one of the districts in Indonesia that has implemented the People's Online Aspiration Service (LAPOR) as a means of accommodating public complaints since 2014, and was initiated by the Presidential Work Unit for Supervision, and the Development Court (UKP4) has become an important pillar of the implementation of Open Government. Indonesia (OGI) in 2014. This study wants to find out whether the LAPOR carried out by the Indragiri Hulu Regency Communication and Information Office is effective in receiving public complaints, following up on community complaints, to the government's response to these complaints, namely whether the government provides solutions to solve the problems at hand. stir up society. The effectiveness of the People's Online Aspirations and Complaints Service (LAPOR) can be seen with the theory of organizational effectiveness measurement from Duncan in Steers, namely Goal Achievement, Integration, and Adaptation. This research uses descriptive qualitative research type, using observation, interview, and documentation techniques. In this study, the subject to be studied is community service, while the object is public complaints through LAPOR. The results showed that the LAPOR applied by the Communication and Information Office of Indragiri Hulu Regency was still ineffective, where the Communication and Informatics Office of Indragiri Hulu Regency had not fulfilled every existing indicator. As the goals that have been previously set have not been maximized. Indicators of integration and adaptation of the Communication and Informatics Office of Indragiri upstream Regency still do not meet the indicators. Lack of commitment from the Indragiri Hulu District Communication and Information Office in resolving problems that occur in the operation of LAPOR, Human Resources in the Communication and Informatics Office are still minimal and less proficient in operating LAPOR, and network connections in the Indragiri Hulu Regency are still uneven which causes several regions cannot access LAPOR. This is an inhibiting factor in implementing LAPOR in Indragiri Hulu Regency.Keywords: Effectiveness, Communication and Informatics Office of Indragiri Hulu Regency, LAPOR